Influence of temperature on textural properties of Rocha pear (Pyrus communis L.) from different sources - Santos, Sandra (2012)
‘Rocha’ pear is the main pear cultivar produced in Portugal and is important in other countries. It is a traditional product, classified as PDO (protected designation of origin). Most pears are consumed directly providing sugars, vitamins, organic acids, polyphenols, minerals and other nutrients. Some are also used for the preparation of fresh juice, canned beverages, alcoholic beverages, jellies and jams. Drying is an efficient way of preserving foods due to the significant reduction in water activity, thus inhibiting microbial growth and undesirable enzymatic modifications. Furthermore, it facilitates handling, storage and transportation, and avoids the use of expensive cooling systems. In this work, pears of the variety Rocha harvested at different orchards (four of the Western region and one of the “Beira Baixa”) were studied, fresh and dehydrated at two temperatures, 40 and 60 ºC, to determine and compare their texture attributes. The texture properties were evaluated by the method of texture profile analysis (TPA), using a texturometer, TE.XT.Plus Stable Micro Systems. The texture parameters evaluated were: hardness, adhesiveness, cohesiveness, elasticity and chewiness. The TPAs were obtained for samples of pears from the different origins analyzed in different orientations, and with or without the skin. In order to characterize each set of pears in relation to their maturation state, their acidity and soluble solids contents were determined, and the maturation index was then calculated.